The complete mitochondrial genome of Proedromys bedfordi Thomas 1911 (Arvicolinae, Rodentia) - Shiqing Wang; Chen Lin; Zhen Wang; Zhangwen Deng (Mitochondrial DNA. Part B. Resources)
The Duke of Bedford’s vole (Proedromys bedfordi Thomas 1911) is distributed only at the border areas of the Sichuan and Gansu Provinces, China. In this study, the first complete mitochondrial genome of P. bedfordi is generated and characterized. The assembled genome is 16,262 base pairs in length and the base compositions present clearly the A-T bias (60.84%). Its genetic constitution and arrangement are consistent with the taxon of the voles, including 13 protein-coding genes, 22 tRNA genes, 2 rRNA genes, and 2 main non-coding regions, D-loop region and OL region. This mitochondrial genome will be a significant supplement for the genus Proedromys and whole mitogenome phylogenetic analysis provided insights into further evolutionary research of the subfamily Arvicolinae.